Antimicrobial effects of some mono- and bishydrazones - Valent, M; Zemek, J; Pódová, M; Kucár, S (Folia microbiologica, 1987)
Antibacterial, antifungal and antiprotozoal effects of nine mono- and bishydrazones of glycolaldehyde, glyoxal, methoxyacetaldehyde and glutaraldehyde were studied using eight model organisms. It was found that bishydrazones are much more efficient antimicrobial agents than monohydrazones in the case of all model microorganisms.
Keywords: Biotransformation; Hydrazones; Staphylococcus aureus; hydrazony; Saccharomyces cerevisiae; Candida albicans; antibakteriální látky; Phenylhydrazines; Escherichia coli; Anti-Infective Agents; Trichomonas vaginalis; Animals; biotransformace; Pseudomonas aeruginosa; Bacillus; fenylhydraziny; Anti-Bacterial Agents; zvířata; Micrococcus; antiinfekční látky